Fresno County Bar Association Bernie Witkin Luncheon at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy, Judge James Paige, Jim Christiansen, Judge Hollis Best, Bernie Witkin, Justice Jay Ballantine, and N.A. "Chad" Chaderjian, the Secretary of the California Youth and Adult Correctional Agency Chad